Investigations into Hybrid Magneto-hydrodynamic (MHD) Antenna (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Dielectric Resonator Antennas (DRAs) have received lots of attention in the last two decades due to several attractive characteristics such as high radiation efficiency, light weight, and low profile. There is also increasing challenges for the design of high bandwidth and multi-bands antennas which can be achieved using MHD Antennas for high speed and reconfigurable applications in wireless communication. In this work the objective is to design and develop a cylindrical MHD antenna with circular patch and two annular rings. Magneto-hydrodynamics (MHD) Antenna is a Fluid based Antenna in which the fluid resonator provides excellent coupling of RF energy into fluid. Fluid resonator volume, chemical properties, electric field and magnetic fields are the factors of resonant frequency, gain and return loss. The proposed antenna shall be tuned in the wide band of frequency range between 7.9 – 27 GHz. Simulations using HFSS and measurements have been carried out in respect of design prototype for ‘Air’ and BSTO (Barium Strontium Titanate Oxide) microwave fluid. The findings in this work that the Fluid Resonator based hybrid approach for antenna enhances the bandwidth by a large factor and annular rings with circular patch in proper geometry provides multiband operation. Variation in the volume of the fluid shifts the resonant frequency of the solid structure in the wideband. When magnetic field is applied, significant improvement has been noticed in return loss of the proposed antenna.